ByzRev 07.2025.052: Batu Bayülgen – Turgut Saner, Architectural Description of Byzantine Remains in Istanbul.: Excavations and Surveys in the City within the Walls (1927–2021) (GABAM Studies 13). Istanbul: Koç University Press 2025. - Niewöhner, Philipp (The Byzantine Review, 2025)
Batu Bayülgen – Turgut Saner, Architectural Description of Byzantine Remains in Istanbul. Excavations and Surveys in the City within the Walls (1927–2021) (GABAM Studies 13). Istanbul: Koç University Press 2025. xxii + 696 pp. and 44 plans. – ISBN 978-625-943349-3